Konsep Jiwa Perspektif Ibn Sīnā - Jarman Arroisi; Rahmat Ardi Nur Rifa Da'i (Islamica: Jurnal Studi Keislaman, 2019)
The soul is one of the topics that really attracts the attention of Muslim and Western scientists. Not a few of those who spend their time to study this problem. However, the study of the soul in the West is not based on religion. In contrast to Muslim scientists who make religion as the footing. This paper intends to discuss the concept of the soul emphasized by one of the Muslim scientists, Ibn Sīnā. By using the descriptive-analysis method, this study produces three important conclusions. First, the soul is the initial perfection to make a real human being. Second, the soul is eternal and does not go along with the destruction of the body. Third, when the soul is separated from the body and is eternal, it has a degree of happiness and misery. To reveal more deeply about the nature of the soul and its existence is very important to discuss.